A vitamin-B2-sensing mechanism that regulates gut protease activity to impact animal’s food behavior and growth - Bin Qi; Marina Kniazeva; Min Han (eLife, 2017)
To survive challenging environments, animals acquired the ability to evaluate food quality in the intestine and respond to nutrient deficiencies with changes in food-response behavior, metabolism and development. However, the regulatory mechanisms underlying intestinal sensing of specific nutrients, especially micronutrients such as vitamins, and the connections to downstream physiological responses in animals remain underexplored. We have established a system to analyze the intestinal response to vitamin B2 (VB2) deficiency in Caenorhabditis elegans, and demonstrated that VB2 level critically impacts food uptake and foraging behavior by regulating specific protease gene expression and intestinal protease activity. We show that this impact is mediated by TORC1 signaling through reading the FAD-dependent ATP level. Thus, our study in live animals uncovers a VB2-sensing/response pathway that regulates food-uptake, a mechanism by which a common signaling pathway translates a specific nutrient signal into physiological activities, and the importance of gut microbiota in supplying micronutrients to animals.